INCREASING CUSTOMER LOYALTY THROUGH FACILITY AND SERVICE - Suwarsito, Suwarsito; Hidayat, Aris; Herawati, Niken (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This research aims to explain the influence of variable quality service and satisfaction towards customer loyalty Wuzzy Net in Pabuaran. The method of collecting data in this study uses survey methods through questionnaires. Based on the results of this research analysis, indicating that the facility significantly affects the loyalty of customers, shown from the value of test significance t = 0.000 smaller than Î± = 0.05 with regression coefficient = 2,527. Service quality significantly affects customer loyalty is demonstrated with a test significance value of T = 0.000 smaller than Î± = 0.05. The quality of service and the simultaneous satisfaction have significant effect on customer loyalty, shown from the value of test significance F = 0.000 smaller than Î± = 0.05 and are able to have contributions to customer loyalty variables of 0504 or 51.7%. The remaining 48.3% are influenced by other variables not analyzed in this study.